Utilization of Traditional Medicinal Plant Species in Seberang Pebenaan Village, Indragiri Hilir Regency, Riau Province. - Megawati; Aini Qomariah Manurung; Suraida (UIN Sulthan Thaha Saifuddin Jambi, 2024)
Community knowledge about the traditional medicinal plants of Seberang Pebenaan Village has never been published. Traditional medicine is just a memory from parents. If this knowledge is not documented, over time it will slowly disappear, and the next generation will no longer be able to preserve the knowledge about medicinal plants from generation to generation. This research aims to find out the type of plant, how to process medicinal plants. The type of research used is descriptive qualitative with 50 subjects. Data collection techniques using observation sheets, interviews that have been validated by experts according to their field. The results of this research show that there are 25 families of 39 plant species. The part of the organ that is most widely used is the leaves, which are processed by boiling, grating, pounding, kneading, and squeezing directly.